(3GdQSGdI GdOGeZI ddQO Ydi GdaGSbs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdHGQ GdYdi SHMGfg CeG HYO CjOce Gdehdi HJCjjOg Efg hQO Edi cJGH Cdag HYV GdfUjQjI GdcGaQjf s
(3BNQgG (B:s
(3ef EQJcGH GdCghGA hGdahGMT hGdTghGJ GdHgjejI hEJHGY GdefcQGJ hGdMeO hGdTcQ dehdGfG hMOg hgh MSfHG hfYe GdfUjQ GdeYjf JeJ GdQSGdI hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B16s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds